A Study to Determine if South African Medical - Van Niekerk, Diederik Johannes (My University, 2006)
The prescription habits of general practitioners are continually under the scrutiny of ethical critics. There are numerous factors that influence a practitioner’s decision as to which antihypertensive agents to prescribe for the treatment of hypertension. As outlined in various international and national guidelines for the management of hypertension, the recommended treatment depends on ethnicity, current life-style, diet, smoking, age, gender, family history and possible underlying or secondary conditions such as diabetes mellitus, heart failure, isolated systolic hypertension, myocardial infarction, pregnancy, and evidence of coronary artery disease (CAD), stroke or peripheral vascular disease. Currently the control of blood pressure in patients with hypertension is far from optimal with over 70% of hypertensive patients being reported as having imperfect control. A number of factors related to the patient, the practitioner or the medication may explain the high incidence of inadequate blood pressure control. One possible explanation for the poor control of blood pressure may be that practitioners fail to comply with the guidelines. Hence the aim of my study was firstly to determine whether a practitioner’s decision as to which medication to prescribe in the treatment of hypertension is influenced by the Southern African Hypertension Society Guidelines. Secondly, in an attempt to assess the validity of the results of the primary analysis, the actual prescription habits (MediCross® database) were assessed and compared to the general practitioner’s recall of their prescription habits. Questionnaires were distributed to 320 MediCross® practitioners and prescription habits were identified and substantiated by the screening of an existing MediCross® database. I chose as my sample MediCross® general practitioners, as they are demographically representative of all major urban areas in South Africa; likely to be open-minded to supporting research and answering questionnaires (as MediCross® is part of a Clinical Research Site Management Organisation); and I had access to the database of the prescriptions made by MediCross® practitioners hence enabling me to fulfil my second objective. However, it must be kept in mind that these practitioners are representative of general practitioners in urban areas only (as the title of my research report indicates). My results show that 33.1% adhere to the guidelines (when a non-conservative definition of diuretics is used); 27% have heard of the guidelines and have a copy of them. When asked to give their own opinion however, 39% thought they adhered to the guidelines. The results also show that ACE inhibitors are the most commonly prescribed drug class for uncomplicated hypertension but a comparison to a MediCross® database, of which the quality is questionable, does not support this. As the response rate to the questionnaires was only 24.7%, these results are only a pilot study; however they suggest that few general practitioners use the guidelines or even have a copy of the guidelines. This pilot study suggests that the guidelines need to be distributed more widely. Furthermore the general practitioners that responded to the questionnaire indicated that the management of hypertension is difficult in that there is no single treatment regimen appropriate for all populations and each different - 5 - patient. It was also their view that clinical guidelines for the management of hypertension should more accurately reflect the uncertainty of when to initiate treatment and individual variation if they are going to take these guidelines seriously and comply with them.
0107750D Masters Research - Faculty of Health sciences
Keywords: Medical; prescription; practitioners; hypertension; myocardial